Exploring stimuli-responsive elastin-like polypeptide for biomedicine and beyond: potential application as programmable soft actuators - Noh, Yeongjin; Son, Eunjoo; Cha, Chaenyung (Frontiers in Bioengineering and Biotechnology, 2023)
With the emergence of soft robotics, there is a growing need to develop actuator systems that are lightweight, mechanically compliant, stimuli-responsive, and readily programmable for precise and intelligent operation. Therefore, “smart” polymeric materials that can precisely change their physicomechanical properties in response to various external stimuli (e.g. pH, temperature, electromagnetic force) are increasingly investigated. Many different types of polymers demonstrating stimuli-responsiveness and shape memory effect have been developed over the years, but their focus has been mostly placed on controlling their mechanical properties. In order to impart complexity in actuation systems, there is a concerted effort to implement additional desired functionalities. For this purpose, elastin-like polypeptide (ELP), a class of genetically-engineered thermoresponsive polypeptides that have been mostly utilized for biomedical applications, is being increasingly investigated for stimuli-responsive actuation. Herein, unique characteristics and biomedical applications of ELP, and recent progress on utilizing ELP for programmable actuation are introduced.